Measurements of Energetic Proton Transport through Magnetized Plasma from Intense Laser Interactions with Solids - Clark, E; Krushelnick, K; Davies, JR; Zepf, M; Tatarakis, M; Beg, F; Machacek, A; Norreys, P; Santala, M; Watts, I; Dangor, A (2000)
Protons with energies up to 18 MeV have been measured from high density laser-plasma interactions at incident laser intensities of 5 × 1019 W/cm2. Up to 1012 protons with energies greater than 2 MeV were observed to propagate through a 125 μm thick aluminum target and measurements of their angular deflection were made. It is likely that the protons originate from the front surface of the target and are bent by large magnetic fields which exist in the target interior. To agree with our measurements these fields would be in excess of 30 MG and would be generated by the beam of fast electrons which is also observed.